2017
DOI: 10.1158/1078-0432.ccr-16-2598
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Purity as an Underlying Key Factor in Glioma

Abstract: Glioma tissues consist of not only glioma cells but also glioma-associated nontumor cells, such as stromal cells and immune cells. These nontumor cells dilute the purity of glioma cells and play important roles in glioma biology. Currently, the implications of variation in glioma purity are not sufficiently clarified. Here, tumor purity was inferred for 2,249 gliomas and 29 normal brain tissues from 5 cohorts. Based on the transcriptomic profiling method, we classified CGGA and TCGA-RNAseq cohorts as the RNAse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
298
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 325 publications
(346 citation statements)
references
References 49 publications
44
298
4
Order By: Relevance
“…According to histopathologic classifications, GBM had the highest SLAMF8. In five molecular entities, as previously reported, SLAMF8 was enriched in tumors of patients with wild‐type IDH lower grade glioma (LGG) and IDH wild‐type GBM (Figure A). These expression trends of SLAMF8 were validated in the TCGA cohort (Figure S1A).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…According to histopathologic classifications, GBM had the highest SLAMF8. In five molecular entities, as previously reported, SLAMF8 was enriched in tumors of patients with wild‐type IDH lower grade glioma (LGG) and IDH wild‐type GBM (Figure A). These expression trends of SLAMF8 were validated in the TCGA cohort (Figure S1A).…”
Section: Resultssupporting
confidence: 74%
“…Glioma purity and infiltrated immune cell components are reported to have important clinical and biological implications. Lower purity means malignancy progression, poor prognosis, and enhanced immune phenotype . SLAMF8 was closely related to immune score, stromal score, and glioma purity.…”
Section: Discussionmentioning
confidence: 94%
“…Lowpurity gliomas were characterized by intensive local immune phenotypes and correlated with a poor prognosis. 23 Therefore, we applied the ESTIMATE algorithm to predict tumor purity using gene expression profiles 26 and found a significant increase in ESTIMATE scores in the high-risk group (Figure S7), indicating that a greater presence of inflammatory microenvironment components is associated with progressive tumorigenesis. 27 In addition, we analyzed the 30-amino acid metabolism-related genes and proteins in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Functional annotation of the 30‐gene signature showed that biological functions of angiogenesis, cell adhesion and immune response may contribute to patients’ high risk and poor clinical outcome. Low‐purity gliomas were characterized by intensive local immune phenotypes and correlated with a poor prognosis . Therefore, we applied the ESTIMATE algorithm to predict tumor purity using gene expression profiles and found a significant increase in ESTIMATE scores in the high‐risk group (Figure ), indicating that a greater presence of inflammatory microenvironment components is associated with progressive tumorigenesis …”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing library was constructed as previously published study . Briefly, RNA was extracted from the frozen tissue sample, and the RNA‐seq library was constructed and subsequently sequenced on the Illumina HiSeq 2000 platform (Illumina, San Diego, CA, USA) using 101‐bp pair‐end sequencing strategy.…”
Section: Methodsmentioning
confidence: 99%